Three-Dimensional Fe3O4@Reduced Graphene Oxide Heterojunctions for High-Performance Room-Temperature NO2 Sensors - Zou, Cheng; Hu, Jing; Su, Yanjie; Shao, Feng; Tao, Zejun; Huo, Tingting; Zhou, Zhihua; Hu, Nantao; Yang, Zhi; Kong, Eric Siu-Wai; Zhang, Yafei (Frontiers in Materials, 2019)
Metal oxide/reduced graphene oxide (RGO) heterojunctions have been widely used to fabricate room-temperature gas sensors due to large specific surface areas of RGO nanosheets and enhanced carrier separation efficiency at the interface. However, the sheet stacking of RGO nanosheets limits the full utilization of metal oxide/RGO heterojunctions. Herein, we demonstrate a high-performance room-temperature NO2 gas sensor based on 3D Fe3O4@RGO p-n heterojunctions with core-shell structure, which were synthesized by self-assembly method and further reduction. The effect of different Fe3O4/RGO ratios and the relative humidity on the sensing performances have been investigated. The experimental results suggest that the 3D Fe3O4@RGO sensor exhibits a good selectivity and high sensitivity of 183.1% for 50 ppm NO2, which is about 8.17 times higher than that of the pure 2D RGO sensor. When exposed to 50 ppb of NO2, the response value still reaches to 17.8%. This enhanced sensing performance is mainly ascribed to the formed heterojunctions and the larger surface area of RGO nanosheets. This 2D to 3D heterostructures strategy provides a general route to fabricate ultrahigh-performance room-temperature RGO-based gas sensors.